SERIODIAGNOSIS AND ELECTRON MICROSCOPY OF BEAN COMMON MOSAIC VIRUS (BCMV) INFECTING COWPEA IN SOUTHERN KARNATAKA, INDIA - B. S. PAVITHRA; KEDARNATH; H. M.RENUKA.; H. A. PRAMEELA; K. T. RANGASWAMY (The Bioscan, 2015)
A Survey was carried out in eight districts of southern Karnataka, India to assess the incidence of bean common mosaic virus-black eye cowpea strain on cowpea (BCMV). Plants showing virus like symptoms were serologically tested with direct antigen coating enzyme- linked immune sorbent assay (DAC-ELISA) against potyvirus antisera, to confirm the virus. The virus was readily transmitted by sap inoculation as well as through Aphids to the cowpea cv. C-152 under glass house conditions. We observed systemic infection in green gram, black gram, soybean, French bean and groundnut and necrotic local lesions on Chenopodium amaranticolor. This virus is long flexuous filamentous particles approximately measuring 952nm in size.